2022
DOI: 10.1007/s00330-022-08952-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning-based 3D super-resolution MRI radiomics model: superior predictive performance in preoperative T-staging of rectal cancer

Abstract: Objectives To investigate the feasibility and efficacy of a deep-learning (DL)-based three-dimensional (3D) super-resolution (SR) MRI radiomics model for preoperative T-staging prediction in rectal cancer (RC). Methods Seven hundred six eligible RC patients (T1/2 = 287, T3/4 = 419) were retrospectively enrolled in this study and chronologically allocated into a training cohort (n = 565) and a validation cohort (n = 141). We conducted a deep-transfer-learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…( 71 ) also conducted a related study and showed that AI performed far better than experienced gastrointestinal pathologists. In addition, CT- or MRI-based imaging histology has many applications, including assessing pathological responses after radiotherapy or chemotherapy ( 72 ) and predicting colon cancer infiltration and metastasis ( 73 , 74 ). The duration of keyword bursts was long before 2016 and became shorter after 2016 ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…( 71 ) also conducted a related study and showed that AI performed far better than experienced gastrointestinal pathologists. In addition, CT- or MRI-based imaging histology has many applications, including assessing pathological responses after radiotherapy or chemotherapy ( 72 ) and predicting colon cancer infiltration and metastasis ( 73 , 74 ). The duration of keyword bursts was long before 2016 and became shorter after 2016 ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al constructed a threedimensional super-resolution model based on deep learning to enhance the z-resolution of T2W images, with an AUC of 0.86. 23 However, this research was limited to manual segmentation. Our work employs a multi-parametric MRI image fusion approach, extracting features from the ROI of the tumor and surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although there have been a few studies that have utilized deep learning technology to predict the preoperative T-stage of rectal cancer, most of these studies have only focused on using a single imaging sequence, such as ADC or T2W. 23,24 For instance, Hou et al investigated a deep-learning model for generating the super-resolution image and extracted radiomics features extracted to predict preoperative T-staging. 23 Wang et al used a support vector machine (SVM) model to predict the T-stage of rectal cancer on the T2W image.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, deep learning has shown promising value in image analysis to assist the clinical decision on cancer or other treatment [ [16] , [17] , [18] , [19] ]. Currently, deep learning-based tools have been developed for diagnosis of disease status in the serial management of patients by using multiple types of medical image [ [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%